Antihypertensive effect of spent brewer yeast peptide. (January 2019) - Amorim, M.; Marques, C.; Pereira, J.O.; Guardão, L.; Martins, M.J.; Osório, H.; Moura, D.; Calhau, C.; Pinheiro, H.; Pintado, M.
Graphical abstract: Highlights: In vitro antihypertensive and antioxidant effect of hydrolyzed brewer´s yeast fractions. A short-term oral antihypertensive effect of hydrolyzed brewer´s yeast fractions. low molecular weight fraction causes decrease in blood pressure of SHR. Yeast peptide fraction with identified novel yeast peptides SPQW, PWW and RYW. Valorization of spent brewer´s yeast for management of hypertension. Abstract: Numerous studies have investigated dietary approaches to prevent chronic lifestyle-related diseases, including hypertension. Spent brewer's yeast is the second largest byproduct originated by the brewing industry and it deserves considerable attention because of its high nutritional value, ca. 40% of its dry mass is rich in protein which can be hydrolyzed into biologically active peptides. To upgrade this byproduct, the aim of this study was initially in vitro assessment of biological properties, e.g. ACE inhibition and antioxidant activity, and then, the in vivo effect in short-term oral antihypertensive effect of hydrolyzed yeast fractions on a well characterized model to study hypertension - Spontaneously Hypertensive Rats (SHR). Here, it was demonstrated that the fraction with molecular weight below 3 kDa containing tri and tetra- peptides with hydrophobic amino acid residues – SPQW, PWW and RYW, causes the most noticeable decrease in systolic, diastolic and mean blood pressure of SHR and shows highest antioxidant effect. These properties highlight the potential use of yeast extract as nutraceutical or functional food ingredient for the management and treatment of hypertension with antioxidant effect.